A Sinking ship a documentary on the conditions of the workers of Hanjin Heavy Industries and Construction-Philippines under Duterte administration - Vizcarra, Frances Samantha M.
Hanjin Heavy Industries and Construction Co. Ltd. (HHIC Co. Ltd.) of South Korea, the fifth largest ship-making facility in the world, established its presence in the Philippines on February 2005 during President Gloria Macapagal-Arroyo's term. The manufacturing facility is located in Subic Bay, formerly a past US Naval Base, and is occupying 30 hectares of land with a 50-year contract of operation in the Philippines. Hanjin has provided job opportunities to thousands of Filipinos. However, in the span of 13 years since the start of its operation, the extent of violations of both local and internationally recognized labor standards is alarming. Unsafe labor practices and inhumane workplaces have resulted to numerous casualties. The workers' right to organize and to bargain collectively was dealt with harassment and union busting. Alongside these incidents, contractualization is still which is prevalent among the workers of Hanjin and is becoming a worsening trend in the workforce.